2022
DOI: 10.15826/chimtech.2022.9.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transformations of bismuth (III) tartrates

Abstract: The processes of oxidative thermolysis of bismuth tartrates [Bi(NO3)(C4H4O6)]·3H2O and BiC4H3O6·H2O precipitated from bismuth nitrate solutions was studied by the methods of X-ray diffraction, thermal analysis, IR spectroscopy and chemical analysis. The staging of thermal transformation processes was determined. Morphological studies of initial precursors and the final products of their thermal transformations were carried out. The expediency of obtaining fine-crystal powders of the tetragonal bismuth oxide mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Bismuth tartrate precursors are also used to produce bismuth oxides [9] and bismuth-based materials [10,11]. We have investigated the thermal decomposition of bismuth tartrate [Bi(NO3)(C4H4O6)]·3H2O obtained by adding a bismuth solution in nitric acid to a solution of L(+)-tartaric acid [12]. It has been shown that thermolysis of [Bi(NO3)(C4H4O6)]·3H2O in air atmosphere for 6 h at 300 °C with preliminary holding at lower temperatures produces a mixture of tetragonal bismuth(III) oxide and bismuth(III) oxocarbonate β-Bi2O3/(BiO)2CO3.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth tartrate precursors are also used to produce bismuth oxides [9] and bismuth-based materials [10,11]. We have investigated the thermal decomposition of bismuth tartrate [Bi(NO3)(C4H4O6)]·3H2O obtained by adding a bismuth solution in nitric acid to a solution of L(+)-tartaric acid [12]. It has been shown that thermolysis of [Bi(NO3)(C4H4O6)]·3H2O in air atmosphere for 6 h at 300 °C with preliminary holding at lower temperatures produces a mixture of tetragonal bismuth(III) oxide and bismuth(III) oxocarbonate β-Bi2O3/(BiO)2CO3.…”
Section: Introductionmentioning
confidence: 99%